(untitled) (Ustozlar uchun, 2026)
This study investigates the integration of information and communication technologies (ICT) in pedagogical activities at secondary and preschool education levels. Drawing on a mixed-methods approach encompassing a survey of 420 educators across Uzbekistan and an analysis of global best practices, the research reveals significant correlations between ICT adoption and improved student engagement, academic performance, and 21st-century skill development. The study identifies key barriers — including insufficient infrastructure, limited teacher training, and lack of localized content — and proposes evidence-based recommendations. The findings affirm that systematic ICT integration, supported by institutional policy and professional development, holds transformative potential for modern Uzbek pedagogy.